COGNITIVE AND ONTOLOGICAL ESSENCE OF AXIOLOGICAL DOMINANTS AND PRINCIPLES OF THEIR TAXONOMY IN DIACHRONIC AND SYNCHRONIC REVIEW - Nataliia Stefanova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The article provides a critical outline of elucidation of the cognitive and ontological essence of axiological dominants with the representatives of different cultures of language and a definition of the principles of their taxonomy in diachronic and synchronic review. The author makes a hypothesis that philosophical and axiological thoughts on this matter have not been homogeneous as in diachronic sense of its study (in particular, in the ancient world, the Middle Ages and Modern period etc.) so as in synchronic segment. It is proved that despite the ancient philosophers' efforts such major value concepts as "Truth", "Good", "Beauty", "Benefit" were left without clear understanding. Thus, they were not differentiated. The attempts of philosophical categorisation and conceptualisation remained to be undertaken by Renaissance scientists and thinkers. However, the notion "value" gets its philosophic status only in the Modern period, which was critical for the development of values taxonomy. The article argues that only after establishment of axiology as an independent philosophical doctrine it was possible to articulate four fundamental principles of the values structure: ontological, which makes it possible to explain scientifically the existential localisation of values and their correlation to human existence; gnoseological (or cognitive), with the help of which we experience values and necessity to study their correlation on the basis of both formalised principle, which is used for general rules of taxonomic hierarchy of values, and conceptual principle, which reveals the essence of values and determines their place in the defined hierarchy. The researcher introduces a new ethnosemiometric vector of axiological issues development directly within linguistics, which will enable to assess axiological dominants with the representatives of different cultures of language relying on the given values taxonomy and values hierarchy.